Effects of English Cued Speech on Speech Perception, Phonological Awareness and Literacy: A Case Study of a 9-Year-Old Deaf Boy Using a Cochlear Implant. (December 2013) - Rees, Rachel; Bladel, Judith
<x content-type="archive" xml:space="preserve">Abstract</x> Many studies have shown that French Cued Speech (CS) can enhance lipreading and the development of phonological awareness and literacy in deaf children but, as yet, there is little evidence that these findings can be generalized to English CS. This study investigated the possible effects of English CS on the speech perception, phonological awareness, and literacy skills of a 9-year-old boy, H.V., who had been exposed to English CS from the age of 1 year and been fitted with a right-sided cochlear implant at 2:03 years. Scores in subtests of standardized assessments for phonological processing, reading, and spelling were in per centile ranks from 50 to 98. Speech perception was assessed in three conditions: auditory alone, audio-visual without CS (AV) and AV with CS (+CS). To hypothesize on the effects of CS on H.V.'s ability to identify English phonemes in novel words he was asked to perceive and write non-words with predictable spellings (e.g. drump) dictated live in the two AV conditions (without and with CS). There was a significant difference between his performance in the two conditions for this dictation test where he scored 100 per cent in the +CS condition and 50 per cent in the AV condition. This suggests CS was helping H.V. to perceive and store novel words and that this effect could have contributed to his development of vocabulary, phonological awareness, and literacy skills that were generally in advance of those expected for his age.